OVERCOMING THE SAND PROBLEM USING THE GRAVEL PACK METHOD IN WELL X IN THE FIELD OF KALREZ PETROLEUM (SERAM) LTD - Lanongko, Wa Riska (Journal of Petroleum and Geothermal Technology, 2024)
In the oil and gas industry, there are often various problems that can interfere with the production process. One of the problems that often occurs is sand problems. The impact of sand problems is to cause damage to downhole and surface equipment. To solve the problem of sand in boreholes, gravel fill can be used. This study was conducted Kalrez Petroleum (Seram) Ltd Field Well X. The purpose of this study was to determine the size of gravel Bagging overcomes sandy issues and determines front and rear production performance Installing a gravel pack and determining the cost comparison of the gravel pack method and sand screening method in terms of cost benefit analysis. Based on the smallest average size of sand grains is 0.024 inch, this size is in accordance with the size of gravel pack in general, namely 16/30 M. Calculation of PI after the use of gravel pack has increased production from 4.4 bbl/psi to 7.8 bbl/psi. Based on the IPR curve before the use of gravel pack, the maximum flow rate (Q max) was 527.4372 bpd, experiencing an increase in the maximum flow rate (Q max) of 907.108 bpd. Based on calculations using cost benefit analysis (Coast Benefit Analysis) between the gravel pack and screen liner methods. The screen liner method can be an alternative to overcome the sand problems, this is because it is seen from the value of the B/C ratio> 1 or 2,3. This means that for every one dollar invested in the method, a savings ratio of 2.3 will be obtained. So the screen liner method is more useful and also efficient. Keywords: Sand problem, downhole and surface equipment, gravel pack, sieve analysis, cost benefit analysis